The Implications of Religious Tolerance and Nationalism Values at Islamic Boarding School - Nicky Estu Putu Muchtar; Imam Suprayogo; T Supriyatno (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to understand how is the implication of religious tolerance and nationalism values applied by each Islamic boarding school. This study was conducted in Islamic boarding schools in Lamongan, which were: IBS of Islam Al-Islam, IBS of Karangasem Muhammadiyah, IBS of Sunan Drajat, and IBS of Modern Muhammadiyah. This study applied a qualitative method, interpreted with a phenomenology approach. The techniques of data collection were through observation, interview and documentation. The results of the study showed the implication of religious tolerance in IBS of Islam Al-Islam, IBS of Karangasem Muhammadiyah, IBS of Sunan Drajat, and IBS of Modern Muhammadiyah possessed the values of acceptance, respect, patience, freedom and cooperation. Meanwhile, differences were found dealing with nationalism values. The IBS of Islam Al-Islam merely possessed the value of respect, though IBS of Sunan Drajat, IBS of Karangasem Muhammadiyah, and IBS of Modern Muhammadiyah possessed the values of self-sacrifice, unity, respect, cooperation, and value of pride of being nation. The findings of this study also led to understanding and implementing the values taught through the spirit of jihad for religion and nation, which was based on the concept of ‘Jihad Kebhinekaan’ synergizing between theories and research findings.